CSU core data dictionary: version 1.0 - Rettig, Patricia J., author; Liu, Shu, author; Hunter, Nancy, author; Level, Allison V., author (Colorado State University. Libraries, 2007)
This document provides guidelines and examples on metadata creation for all Colorado State University Libraries (CSUL) digital projects. It is the collaborative output of the CSUL Metadata Best Practices Task Force's second-phase work.
Keywords: metadata implementation guidelines; digital projects; Metadata; Institutional repositories